Sistem Keseimbangan Robot ERISA Pada Bidang Miring Menggunakan Kontrol PD dan Sensor Fusion - Novian Fajar Satria; Ali Husein Alasiry; Bambang Sumantri; Risma Dian Alamri (Jurnal Rekayasa Elektrika, 2021)
The world of robotics is currently developing; many robots are created to help humans work in carrying out daily activities. Various types of robots have been created, one of which is a type of robot that resembles a human body (humanoid). Humanoid robots are developing in many countries, including Indonesia. In its development, the walking technique is a major factor in making humanoid robots. Humanoid robots have the ability to walk like humans by balancing their body positions while walking, so they don’t fall. In maintaining this balance, a tilt detection system for the robot’s position and a balancing system is needed when the robot is about to fall. So, to overcome this problem, implementation is carried out using the sensor fusion method at the output of the sensors that are used to minimize noise or interference with the sensor output value. The accuracy of the sensor output value on the position angle tilt detector can help the robot provide a balancing act. By implementing a PD control system and sensor fusion consisting of a Kalman filter and a complementary filter, the robot was successfully carried up and down the plane to a maximum slope of 12 °.